2015
DOI: 10.2135/cropsci2014.04.0284
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Genotype Effects on Seed Quality Traits in Winter Oilseed Rape

Abstract: The genetics of seed compounds is complex because seed quality traits might be exclusively determined by the genotype of the female parent or, depending on the genotype of the embryo, may also be affected by the genotype of the pollen parent. For many quality traits of oilseed rape (Brassica napus L.), the influence of the pollen parent is not well known. In this study, two male sterile lines (female parent) were pollinated by 10 genotypes (pollen parent) differing largely in seed quality. Field experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Embryo effect accounted for 21% of the genetic variance and cytoplasmic effect was detectable only at a very low level (Table 7). The present study confirms the earlier findings that the OC of F 1 seeds is mainly controlled by maternal effect, and xenia is weak [11, 13, 45]. Analysis of reciprocal backcrosses demonstrates that maternal, xenia, and cytoplasmic effect can all influence OC (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Embryo effect accounted for 21% of the genetic variance and cytoplasmic effect was detectable only at a very low level (Table 7). The present study confirms the earlier findings that the OC of F 1 seeds is mainly controlled by maternal effect, and xenia is weak [11, 13, 45]. Analysis of reciprocal backcrosses demonstrates that maternal, xenia, and cytoplasmic effect can all influence OC (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to the finding of Hom et al [48]. Earlier studies reported that the OC of F 1 seeds was significantly lower than that of self-pollinated seeds when a HO female was crossed with a LO male, but it was significantly higher than that of self-pollinated seeds when a LO female was crossed with a HO male [11, 12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations